Secondary prevention of antithrombotic therapy in patients with stable cardiovascular disease at high ischemic risk: A network meta-analysis of randomized controlled trials - Zhu, Houyong; Xu, Xiaoqun; Wang, Hanxin; Chen, Qilan; Fang, Xiaojiang; Zheng, Jianwu; Gao, Beibei; Tong, Guoxin; Zhou, Liang; Chen, Tielong; Huang, Jinyu (Frontiers in Cardiovascular Medicine, 2023)
Aims Antithrombotic secondary prevention in stable cardiovascular disease (SCVD) patients at high ischemic risk remains unclear. We compared the efficacy and safety of aspirin monotherapy, clopidogrel monotherapy, ticagrelor monotherapy, rivaroxaban monotherapy, clopidogrel plus aspirin, ticagrelor plus aspirin, and rivaroxaban plus aspirin in the high-risk ischemic cohorts. Methods and results Eleven randomized controlled trials were included (n = 111737). The primary outcomes were major cardiovascular and cerebrovascular events (MACEs) and major bleeding. A random effects model was used for frequentist network meta-analysis. Odds ratio (OR) and 95% credible intervals (CI) were reported as a summary statistic. Compared with aspirin monotherapy, rivaroxaban plus aspirin [OR 0.79 (95% CI, 0.69, 0.89)], ticagrelor plus aspirin [0.88 (0.80, 0.98)], clopidogrel plus aspirin [0.56 (0.41, 0.77)] were associated with a reduced risk of MACEs, but rivaroxaban monotherapy [0.92 (0.79, 1.07)], ticagrelor monotherapy [0.68 (0.45, 1.05)], and clopidogrel monotherapy [0.67 (0.43, 1.05)] showed no statistically significant difference. However, rivaroxaban monotherapy and all dual antithrombotic strategies increased the risk of major bleeding to varying degrees, with ticagrelor plus aspirin associated with the highest risk of major bleeding. The net clinical benefit favored clopidogrel or ticagrelor monotherapy, which have a mild anti-ischemic effect without an increase in bleeding risk. Conclusion The present network meta-analysis suggests that clopidogrel or ticagrelor monotherapy may be recommended first in this cohort of SCVD at high ischemic risk. But clopidogrel plus aspirin or rivaroxaban plus aspirin can still be considered for use in patients with recurrent MACEs.